Odpowiedzi

2010-03-08T19:05:54+01:00
A) 3(a-2) = 3a-6
b) -4(x+y) = -4x-4y
c) -5(-x+1) = 5x-5
d) -3a(1/3-a) = -a+3a²
e) (-t-2s-1)*7 nie było początkowego nawiasu, nie wiem czy dobrze zgadłam gdzie być powinien, wg powyższego będzie: = -7t-14s-7
f) 1/2(2a-4b+1) = a-2b+1/2
g) m(2m+3) = 2m²+3m
h) 3p(2r+5p-1) = 6pr+15p²-3p
i) xy(2x-3y+5) = 2x²y-3xy²+5xy
2010-03-08T19:06:22+01:00
A) 3(a-2) / 3a-6
b) -4(x+y) / -4x-y
c) -5(-x+1) / 5x-5
d) -3a(1/3-a) tego nie wiem
e) -t-2s-1)*7 / -t7-14s-7
f) 1/2(2a-4b+1) / a-2b+0,5
g) m(2m+3) / 2m2+3m
h) 3p(2r+5p-1) / 6pr+15p2-3p
i) xy(2x-3y+5) / 2x2y-3xy2+5xy